Bioremediation of crude oil pollutants in the soil by Pseudomonas aeruginosa and other soil microorganisms (World Journal of Experimental Biosciences, 2023)
Soil pollution with oily residues is one of the biggest challenges facing the environment. Microorganisms, especially Pseudomonas aeruginosa play an important role in decomposing oil in soil. The current study aims to highlight the role of P. aeruginosa and the synergistic effect of other microorganisms in cleaning the soil from oily residues. Here, nine isolates of P. aeruginosa were isolated from soil contaminated with oil. Use biochemical methods and VITIK II technology in identifying the isolates. An oil-contaminated soil model was established in the laboratory, and eight experimental groups were used in the current study; group a, sterilized soil mixed with crude oil and P. aeruginosa (OD600: 0.8); group b, soil mixed with crude oil and P. aeruginosa (OD600: 0.8); group c, sterilized soil mixed with crude oil; group d, soil mixed with 5 ml of crude oil; group e, sterilized soil mixed with waste cooking oil (WCO) and P. aeruginosa (OD600: 0.8); group f, soil mixed with WCO and P. aeruginosa; group g, sterilized soil mixed with WCO; group h, soil mixed with WCO. The results showed that the highest percentage of decrease in WCO and crude oil was found in the soil group that was not sterilized in the presence of P. aeruginosa. A moderate rate of decomposition was also found in soil that had not been sterilized, and also in sterilized soil in the presence of P. aeruginosa. The sterilized soil (only) did not show any significant decrease in the WCO and crude oils. It can be concluded that P. aeruginosa is capable of decomposing WCO and crude oils and the presence of other soil microorganisms has increased the rate of decomposition of oil in the soil, which confirms the synergistic role of microorganisms and P. aeruginosa in decomposing WCO and crude oils.